2010
DOI: 10.3960/jslrt.50.107
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of CD5-Positive Splenic Marginal Zone Lymphoma with Leukemic Manifestation ; Clinical, Flow Cytometry, and Histopathological Findings of 11 Cases

Abstract: Splenic marginal zone lymphoma (SP-MZL) is a rare low-grade B-cell neoplasm that often shows leukemic manifestation. Less than 20% of cases of SP-MZL express CD5. We analyzed 11 cases of CD5-positive SP-MZL with leukemic manifestation. The clinical characteristics of these cases did not differ from those of CD5-negative SP-MZL. Flow cytometry revealed positive results as follows : CD3, 0/9 ; CD5, 11/11 ; CD10, 0/11 ; CD11c, 4/10, CD13, 5/11 ; CD19, 11/11 ; CD20, 10/11 ; CD21, 4/4 ; CD22, 7/7 ; CD23, 5/10 ; CD2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
1
12
1
3
Order By: Relevance
“…Importantly, molecular and cytogenetic findings could help to refine the diagnosis in difficult cases. As previously reported by our group and others, 19,35 CD5 can be expressed in SMZL without clinicopathological, biological or cytogenetic specificity, with the exception of a higher lymphocyte count at the time of diagnosis. Mantle cell lymphoma can be easily eliminated by the absence of cyclin D1 expression and massive macronodular infiltration by small irregular cells.…”
Section: Discussionsupporting
confidence: 74%
“…Importantly, molecular and cytogenetic findings could help to refine the diagnosis in difficult cases. As previously reported by our group and others, 19,35 CD5 can be expressed in SMZL without clinicopathological, biological or cytogenetic specificity, with the exception of a higher lymphocyte count at the time of diagnosis. Mantle cell lymphoma can be easily eliminated by the absence of cyclin D1 expression and massive macronodular infiltration by small irregular cells.…”
Section: Discussionsupporting
confidence: 74%
“…The surface or cytoplasmic light-chain evaluation was the most useful parameter in identifying a B-cell lymphoma, whereas CD5 and CD10 are useful in identifying the different subtypes (1). However, their specificity is not absolute on neoplastic cells, as stands out from data also reported by us in Table 4; in fact they may be absent in FL (CD10 À FL) (37) or can be unexpectedly expressed elsewhere, such as CD5 on some SMZL cases (5,49) and FL (36,39,50,51), CD10 on SLL (50,51), NMZL (43), MCL and MALT (37), and HCL (52), CD5/ CD10 coexpression on DLBCL (35,50,53). These kinds of B-NHL still remain challenging for flow cytometrists, because the lack of a specific phenotype and their great heterogeneity, especially observed among MZL (nodal, splenic, extranodal), SL and LPL, determine their identification mainly on the j/k ratio.…”
Section: Discussionmentioning
confidence: 85%
“…Kojima M et al 12 reported 11 patients with CD5-positive splenic MZL with leukemic manifestation. They found that less than 20% of splenic MZL patients are CD5 positive.…”
Section: Other Cd5-positive Lymphomasmentioning
confidence: 99%